Measuring authorial voice strength in L2 argumentative writing: The development and validation of an analytic rubric. (April 2013) - Zhao, Cecilia Guanfang
Although a key concept in various writing textbooks, learning standards, and writing rubrics, voice remains a construct that is only loosely defined in the literature and impressionistically assessed in practice. Few attempts have been made to formally investigate whether and how the strength of an author's voice in written texts can be reliably measured. Using a mixed-method approach, this study develops and validates an analytic rubric that measures voice strength in second language (L2) argumentative writing. Factor analysis of ratings from six raters on voice strength in a total of 400 TOEFL® iBT writing samples, together with qualitative analysis of four raters' in-depth think-aloud and interview data, points to an alternative conceptualization of voice that sees authorial voice in written discourse as being realized primarily through the following dimensions: (1) the presence and clarity of ideas in the content; (2) the manner of the presentation of ideas; and (3) the writer and reader presence. Implications of such results for L2 writing instruction and assessment are discussed.